PENERAPAN BIMBINGAN KELOMPOK TEKNIK PROBLEM SOLVING TERHADAP REGULASI EMOSI SISWA DI SMPN 2 BUDURAN - Enov Aisyafarah, Aqsani; Setiawati, Denok (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Emotional regulation is a crucial component of adolescent development. High emotional regulation will be related to psychological well-being. This research was conducted to determine the extent to which group guidance services and problem-solving techniques can improve students' emotional regulation abilities. A pre-experimental method and a one-group pretest-posttest design were used in this study. Ten students were selected using a non-random selective sampling method. Data collection was conducted using a questionnaire. Data analysis using a two-tailed Wilcoxon test resulted in an Asymp. Sig. (2-tailed) value of 0.005, which is less than 0.05. The findings indicate that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Given the striking difference between the pretest and posttest results, it can be concluded that students of SMPN 2 Buduran can improve their emotional regulation by using group counseling and problem-solving strategies.This study only tested one group. Further research should be developed with more subjects.